Effectiveness of the Whole-of-Government Approach in Overcoming Cross-Sectoral Problems in Makassar City - Novayanti Sopia Rukmana; Saddam Husain Tamrin (Program Pascasarjana Universitas Negeri Makassar, 2024)
The aim of this research is to evaluate the effectiveness of the Whole-of-Government (WoG) approach in overcoming cross-sectoral problems in Makassar City as well as identify the challenges faced and provide policy recommendations to improve public sector collaboration. The research method used is a literature review, which allows the collection and analysis of various relevant and reliable literature sources. Literature was collected through academic databases such as Google Scholar, JSTOR, and PubMed. The analysis technique used is thematic analysis, where relevant information is grouped into themes that have been identified and synthesized to form a complete picture of WoG effectiveness. The research results show that the main challenges in cross-sector coordination in Makassar City include sectoral egos, lack of effective coordination mechanisms, communication barriers, and lack of resources and capacity. To increase the effectiveness of WoG, this research recommends building a collaborative work culture, developing formal and structured coordination mechanisms, improving communication systems, adequate resource allocation, policy synchronization, and implementing reward systems. It is hoped that the implementation of these recommendations can increase the effectiveness of implementing WoG in overcoming cross-sectoral problems in Makassar City, so that public services can run more optimally and efficiently.